Effects of Plasma Proteins on the Transport and Surface Characteristics of Polysulfone/Polyethersulfone and Asymmetric Cellulose Triacetate High Flux Dialyzers. Issue 11 (17th May 2018) - Kim, Tae Ryung; Hadidi, Mahsa; Motevalian, Seyed Pouria; Sunohara, Takashi; Zydney, Andrew L.
Abstract: Blood‐membrane interactions can have a large impact on the performance of hemodialysis membranes, particularly for high flux membranes in which the membrane itself provides very low resistance to solute transport. The objective of this study was to examine the effects of exposure to serum on the solute clearance and convective sieving characteristics of high flux polysulfone (Optiflux F250NR), polyethersulfone (ELISIO‐25H), and asymmetric cellulose triacetate (SOLACEA‐25H) hemodialyzers using both vitamin B12 and a range of polydisperse dextrans. Zeta potential measurements were used to obtain additional insights into the changes in membrane surface properties. Exposure to serum in a simulated dialysis session caused a significant reduction in both solute clearance and sieving coefficients for the polysulfone/polyethersulfone dialyzers, particularly for the larger molecular weight solutes. In contrast, the transport characteristics of the asymmetric cellulose triacetate dialyzers were almost unchanged after exposure to serum. The zeta potential of the cellulose triacetate membrane became slightly more negative after exposure to serum, consistent with an adsorbed protein layer composed largely of albumin. The net result is that the asymmetric cellulose triacetate dialyzer had dramatically higher clearance of the larger dextrans after exposure to serum, with the clearance and sieving coefficient for a 10 kDa molecular weight dextran being more than an order of magnitude greater than that of the polysulfone/polyethersulfone membranes. These results provide important insights into the expected clinical performance of these high flux dialyzers.